Effectiveness of Non-Pharmacological Intervention to Reduce Perineal Pain In Postpartum Women - Khusniyati, Etik; Heni Purwati; Elies Meilinawati SB (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The morbidity and mortality rates for pregnant, postpartum and postpartum women are still a big problem. One of the factors of this morbidity rate is postpartum pain caused by perineal tears. Pain management has two methods, namely pharmacological and non-pharmacological. The purpose of this study was to determine the effectiveness of non-pharmacological interventions in reducing perineal wound pain in postpartum mothers. The method used in this paper is a literature review. The preparation of the literature review was carried out by searching articles from the Google Scholar and Pubmed databases. The keywords used included non-pharmacological, perineal pain OR reducing perineal pain, and postpartum. The inclusion criteria in this literature search were articles from 2018-2023, articles in Indonesian, articles in English, free full-text articles, original articles and articles on non-pharmacological therapy to reduce perineal wound pain in postpartum mothers. The results of the study, it was obtained the results of several non-pharmacological interventions that were effective in reducing perineal wound pain, namely Papaya Leaf Decoction, Red Ginger, Cinnamon Extract, Aromatherapy (Chamomile Aromatherapy, Lavender Aromatherapy, Lemon Aromatherapy), Sitz Bath Therapy, Compress Ice Gel and Acuyoga Postpartum. Based on the findings of the literature, this non-pharmacological intervention in postpartum mothers has proven effective to be applied in practice and is recommended for health workers.